60.7k views
0 votes
(Number 5)help plzzz

(Number 5)help plzzz-example-1

1 Answer

3 votes

Answer:

See below.

Explanation:

So we want to prove that:


\sqrt8+\sqrt2=3\cdot 2^{(1)/(2)}

First, simplify √8. This is the same as:


\sqrt8=√(4\cdot 2)=\sqrt4\cdot\sqrt2=2\sqrt2

Therefore, our equation is now:


2\sqrt2+\sqrt2=3\cdot2^{(1)/(2)}

Combine like terms on the left:


3\sqrt2=3\cdot 2^(1)/(2)}

The square root of something is the same as taking that number to the one-half power. Thus:


3(2)^(1)/(2)}=3\cdot 2^(1)/(2)}

Rewrite:


3\cdot2^(1)/(2)}\stackrel{\checkmark}{=}3\cdot2^(1)/(2)}

And we're done!

User Simeonovich
by
4.5k points